Parenting policies and support practices : a position paper for the Special Session of Council of Human & Social Development (COHSOD) on Children, Guyana, March 2008 (Caribbean Child Support Initiative St MichaelBB, 2008)
Presents compelling arguments for advocating that member states urgently focus on developing a national framework for action to promote effective parenting practices, increase parenting support services and develop appropriate and relevant parenting policies.
Includes an executive summary prepared by Bridgette Barrett, 14.02.04 C277es